OPTIMALISASI KELEMBAGAAN DAN MANAJEMEN DALAM BUS RAPID TRANSIT SEMARANG - Ahmad Ghoni; Haptiwi Tri Yuniar; Bambang Riyanto; Supriyono Supriyono (Departemen Teknik Sipil, Fakultas Teknik Universitas Diponegoro, 2013)
Bus Rapid Transit Trans Semarang is a means of mass transportation to the transit system that began operating since 2009 as a solution to reduce congestion in the city of Semarang. This research focuses on the optimization and management of institutional BRT Trans Semarang to improve it’s performance. The purpose of this study is to optimize the performance of the organization and management of BRT Trans Semarang with variable types of institutional cooperation BRT operations, and leadership style. Stages of the methodology to do is identify the problem, literature, comparative studies of Trans Jogja, stakeholder’s need analysis, data processing, and formulating policy recommendations. The results showed a number of conditions and institutional and management problems BLU-UPTD Terminal Mangkang as the governing institution of BRT Trans Semarang, among others: 1) Need to changes 3 old buses with 1 BRT so BRT can reduce the congestion effectively and also can incrase BRT load factor. 2) Need 20 fleets BRT to supply the passenger’s demand. So the subsidy is still needed to complete the BRT’s cost operational until the load factor reach 70%. 3) The institutional leadership style BRT is currently 69(minimum criteria is 75). While the percentage of fulfillment of expectations of leaders based employee appraisal is only 70.45(minimum criteria is 75). The recommendation to optimize the organization and management of BRT Trans Semarang are construct BLU so it has flexibility to manage substitution the old moda with BRT, to determine the cost policy that cheaper than old moda’s cost in order to increase load factor, still gets subsidy to keep quality service base on SPM. In additional needs to increase coordination and communication in institution to increase efectivity of institution’s works.